Enhancing Nurses' Knowledge-related Prevention of Sudden Infant Death Syndrome - Mohammed, Safa A. Mohammed; Aziz, Afifa R. Aziz (Iraqi National Journal of Nursing Specialties, 2024)
Objective(s): to enhance nurses' knowledge-related preventing sudden infant death syndrome by applying a nursing program based on updated recommendations of American Academy of Pediatric for a Safe Infant Sleeping Environment (2022).Methods: A quasi-experimental study with two study groups (pre-test, post-test I, and post-test II) carried out at Children's Welfare Teaching Hospitals and The Central Teaching Hospital of Pediatrics in Baghdad City from September 14th, 2023 to February 21th, 2024. The study recruited fifty nurses, divided into two groups equally. The study used the validated Knowledge test instrument with (10) items (multiple choices). An Educational program is built according to American Academy of Pediatric update guidelines for sudden infant death syndrome. Version 26.0 of the Statistical Package of Social Sciences (SPSS) was used to analyze the research's data.Results: The study results indicate that the majority of nurses had a poor level of knowledge (M=0.38) prior to the application of the program, while the post-test showed a good level of knowledge during posttest 1 (M=0.80) and posttest 2 (M=0.69) among nurses in the study group. Compared with the control group, nurses showed fair knowledge during the pretest (M = 0.45), posttest I (M = 0.37), and posttest II (M = 0.38), regarding the prevention of sudden infant death syndrome.Conclusion: This study suggest that the nursing educational program yields tangible positive outcomes on improving nurses' knowledge-related prevention of sudden infant death syndrome.Recommendations: The Iraqi Ministry of Health might benefit from adapting this guide on the prevention of sudden infant death syndrome as a training program for nurses to improve their knowledge of the prevention of sudden infant death syndrome and to conduct further studies on a large sample of nurses in order to disseminate better and apply evidence-based practice.